Conceiving Cuba : reproduction, women, and the state in the post-Soviet era - Andaya, Elise (Rutgers University Press, 2014)
Conceiving Cuba offers an intimate look at how the institutions promoting the well-being of mothers and children, once a cornerstone of the socialist system, collapsed with the fall of the Soviet Union, throwing both individual families and the nation itself into profound crisis. Drawing from years of first-hand observations and interviews, anthropologist Elise Andaya takes us inside the island's households and medical facilities, as they struggle to make do with limited resources and grapple with difficult questions concerning family planning, reproductive health, and the future o.